CHRISTIAN ETHICS VS. CORRUPT ECONOMY - Babasyan, Tigran; Hayrapetyan, Albert (European Scientific Journal, ESJ, 2014)
Christianity as a consummate and the most individualized religion, allows one to best harmonize the relationships between an individual, society, and the state. Christianity roots in the fundamental sentiment of personal responsibility for own thoughts and deeds. That the Christian doctrine has an immense variety of tools to resolve the whole gamut of socio-political issues has been brilliantly evidenced in hosts of victories on a civilization scale. Being a pro-active religion, Christianity has been the driving force behind the groundbreaking, epoch-making processes both at political and scientific level. Christianity has brought about a new model of state economy basing on equity and liberalism. However, having swerved from good intentions, the modern Christian nations are caught in the economic crisis, facing the urgency to regain their economic strength lavished on the rest of civilizations. The only way to reach this is to reconsider Christian values.